Impacts of Selective Logging and Associated Anthropogenic Disturbance on Intact Forest Landscapes and Apes of Northern Congo - Morgan, David; Strindberg, Samantha; Winston, William; Stephens, Colleen R.; Traub, Cindy; Ayina, Crepin Eyana; Ndolo Ebika, Sydney Thony; Mayoukou, Wen; Koni, David; Iyenguet, Fortune; Sanz, Crickette M. (Frontiers in Forests and Global Change, 2019)
The tropical forests of Western Equatorial Africa are home to extraordinary biodiversity, including sympatric chimpanzees (Pan troglodytes troglodytes) and western lowland gorillas (Gorilla gorilla gorilla). The region is also comprised of significant stands of Intact Forest Landscapes (IFL) that are in rapid decline. As part of a regional monitoring effort, we partnered with local government officials, conservation NGOs, and the timber company working in the region to assess ape abundances in relation to habitat characteristics and anthropogenic disturbances and compare IFL and non-IFL areas in the Sangha Trinational landscape, Republic of Congo. We found that chimpanzees and gorillas occur at high densities in IFL, as well as non-IFL. To better understand how selective logging changes floristic factors, we compared herb and tree densities from botanical surveys conducted in IFL and non-IFL. IFL had higher tree stem densities and less terrestrial ground herbs than logged habitats. However, few ape resources were logged in this extraction cycle and areas with tree stems removed had higher abundances of ape preferred terrestrial herbs, which may contribute to the elevated ape abundance estimates. Floristic differences in logged forest were however identified to coincide with differences in ape resource use. The chimpanzee tree nesting niche was reduced in non-IFL as night nests were constructed significantly closer to the ground than in IFL. Whereas gorilla nest height locations did not differ significantly between IFL and non-IFL. To identify other potential anthropogenic impacts, we assessed direct and indirect impacts of road expansion and illegal hunting on wildlife in these remote areas. Increased access to IFL that facilitates illegal hunting raises concern for protecting wildlife across Western Equatorial Africa. We urge that the results of biodiversity assessments and strategic aspects of long-term protection should be taken into account when identifying conservation set-asides and maintaining diverse states of modified forests. Finally, the results of our monitoring efforts are provided as evidence of the value of long-term collaborations among local stakeholders, government officials, conservation agencies, and industrial partners to improve the implementation of certification standards and biodiversity conservation initiatives.